Changes in alcohol intoxication-related ambulance attendances during COVID-19: How have government announcements and policies affected ambulance call outs? - Rowan P. Ogeil, PhD; Debbie Scott, DHealthSc; Agatha Faulkner, MPH; James Wilson, PhD; Naomi Beard, MSc(Epi); Karen Smith, PhD; Victoria Manning, PhD; Dan I. Lubman, PhD (The Lancet Regional Health. Western Pacific, 2021)
Background: In response to COVID-19, government-mandated health directives including widespread lockdowns were implemented. Changes in alcohol purchasing were reported, with growing concern that alcohol may be consumed as a way to cope with pandemic-associated stressors. Hitherto, there have been limited studies examining alcohol-related harms, including acute harms requiring an ambulance, and their relationship to government announcements or policies related to COVID-19. Methods: Analyses were conducted between January and September 2020, with matched months in 2019, using Victorian data from the National Ambulance Surveillance System in Australia. Interrupted time series (ITS) models with odds ratios (OR) were used to map alcohol-related harms as a function of government policies for both metropolitan and regional areas. Findings: A total of 43,003 alcohol intoxication-related ambulance attendances occurred between January 2019 and September 2020. Attendances in the home increased in 2020 by 9% compared to matched 2019 months. The most socioeconomically advantaged cases showed the highest percentage change. ITS models showed decreased odds of alcohol-related attendances at the beginning of each COVID-19 wave in metropolitan (OR:0•77; 95%CI: 0•71-0•83; p<0•001) and regional Victoria (OR: 0•72; 95%CI: 0•67-0•79, p<0•001) separately, and increased odds following the introduction of harsher restrictions in metropolitan Melbourne (OR:1•07; 95%CI:1•01-1•11, p=0•005). A 19% increase in odds of alcohol-related harms was observed at the end of the second wave lockdown period in regional Victoria (OR:1•19; 95%CI: 1•01-1•41, p=0•004). Interpretation: Alcohol-related attendances during COVID-19 restrictions showed a displacement to home settings. Changes in patterns of harms were evident in specific sociodemographic groups, and geographic regions when mapped to government health directives. This study is one of the first to investigate alcohol-related harms at the population level in response to a global pandemic. Funding: Commonwealth Department of Health and Victorian Department of Health.